Bonds of Alliance : Indigenous and Atlantic Slaveries in New France - Rushforth, Brett (Book collections on Project MUSE., 2012)
Based on thousands of French and Algonquian-language manuscripts archived in Canada, France, the United States and the Caribbean, Bonds of Alliance bridges the divide between continental and Atlantic approaches to early American history. By discovering unexpected connections between distant peoples and places, Rushforth sheds new light on a wide range of subjects, including intercultural diplomacy, colonial law, gender and sexuality, and the history of race."--Univ. of North Carolina Press.